Global estimate of Neisseria meningitidis serogroups proportion in invasive meningococcal disease: A systematic review and meta-analysis. (September 2019) - Purmohamad, Ali; Abasi, Elham; Azimi, Taher; Hosseini, Sareh; Safari, Hossein; Nasiri, Mohammad Javad; Imani Fooladi, Abbas Ali
Abstract: Using the PRISMA guideline, 102 studies were included in this study. The highest and the lowest proportion of N. meningitidis serogroups in invasive meningococcal disease (IMD) was for NmB with 48.5% (95% CI: 45–52) and NmX with 0.7% (95% CI: 0.3–1.7). Among the WHO regional offices, serogroup NmW with 57.5% (95% CI: 35–77.5) in Eastern Mediterranean, and NmZ with 0.1% (95% CI: 0–0.9) in America had the highest and the lowest proportion of N. meningitidis serogroups in IMD. NmC with 9.7% (95% CI: 5.6–16.2) and NmB with 9.5% (95% CI: 0.2–3.8) had the highest proportion in 1–4 and <1 year age groups, respectively. Our analysis showed that NmB had the highest proportion of N. meningitidis serogroups in IMD worldwide. However, proportion of N. meningitidis serogroups in IMD varied noticeably across countries and age groups. Therefore, establishing appropriate control guidelines depending on the geographical regions and age groups is essential for prevention of IMD. Highlights: In the pooled analysis, the highest and the lowest proportion of N. meningitidis serogroups in invasive meningococcal disease (IMD) were for NmB with 48.5% (95% CI: 45–52) and NmX with 0.7% (95% CI: 0.3–1.7).. Our results demonstrated that proportion of N. meningitidis serogroups in IMD varied noticeably across countries and age groups. Establishing appropriate control guidelines depending on the geographical regions and age groups is essential for prevention of IMD.